Vanadium dioxide-based tunable broadband metamaterial absorber in the terahertz - Yuqi Zhu (Materials Research Express)
This study presents a three-layer broadband absorber comprising a vanadium dioxide (VO _2 ) layer at the top, a polytetrafluoroethylene layer in the middle, and a gold film at the bottom. Absorption curves were calculated using the multiple-reflection principle and impedance matching theory, and the obtained results were consistent with the simulation results. According to simulation results, within the range of controllable conductivity of VO _2 , the absorption rate of the as-developed structure varied from 1.5% to 99.8%, with the bandwidth extending from 0 THz to 5.19 THz. The metamaterial maintained > 75% absorption across the frequency band for incident angles up to 45°, with the absorption rate varying for different polarization angles. The as-developed metamaterial exhibited the characteristics of wide-angle incidence and polarization sensitivity and has excellent application prospects in the domains of medicine, military, and communication.